TRANSLATION PEDAGOGY VERSUS PEDAGOGICAL TRANSLATION IN LANGUAGE LEARNING - Nik Zaitun Nik Mohamed; Ameiruel Azwan Ab Aziz; Kamsilawati Kamlun; Irma Wani Othman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This conceptual paper presents the review of literatures of a study related to Translation in Language Teaching (TILT) and Translation Training, It reviews related literature on translation theories and practices in bilingual/multilingual classrooms as well. The interplay of translation, multilingualism, multiculturalism and globalisation in today’s ESL pedagogical reality demands translation to be employed in improving students’ English language proficiency. Unfortunately, research indicates that teachers do not possess adequate knowledge on appropriate translation models to enable them to perform translation in language teaching (TILT). As a result, they ended up employing unplanned code switching and code-mixing techniques throughout their English language lessons. Studies have shown that translation educators also do not possess adequate competencies in training language teachers to translate due to discrepancy between the chosen modules and teachers’ motivation. As a result, teachers failed to understand the purpose of such training. This conceptual paper, thus, attempts to conjure up two important concepts in translation studies: Pedagogical translation and translation pedagogy. Translation Pedagogy refers to the acquired knowledge on how to translate, whereas pedagogical translation refers to the actual process or practice of translation either in written or verbal form. The relevance of these two concepts in TILT are highlighted and discussed throughout this paper. A translation model is suggested as a guideline in providing training in TILT area. The result of this upcoming study may provide a direction in translation training for language teachers in Malaysia. It suggests that the concepts of Pedagogical Translation (PT) and Translation Pedagogy (TP) should be incorporated into translation training modules. By doing so, both translation trainers and teacher trainees are able to understand the actual processes of translation itself in TILT.